Using Murojaah Wheel Media to Aid Qur'an Memorization in Young Children - W, Dienar Halimah; Rochmah, Luluk Iffatur (Universitas Muhammadiyah Sidoarjo, 2024)
The ability to read and memorize the Qur'an is crucial for young children, providing long-term benefits for their spiritual and cognitive growth. However, there is a growing concern about children’s decreasing engagement with the Qur'an due to the influence of modern distractions. This study addresses this gap by exploring the use of Murojaah wheel media as a tool to facilitate Qur'an memorization among children aged 4-5 years at As-Shoffah Early Childhood Education. The aim is to evaluate the effectiveness of this media in enhancing memorization skills. Using a quantitative ex-post facto design, the study involved 12 students selected through a saturated sampling technique. A questionnaire administered to teachers served as the primary instrument for data collection. Data were analyzed using simple linear regression with JASP software version 18.0. The results revealed a significant positive correlation between the use of the Murojaah wheel media and the students' ability to memorize the Qur'an (F=8.943, p=0.014). The novelty of this research lies in its focus on the application of interactive learning media in Islamic education for young children. Implications of these findings suggest that incorporating Murojaah wheel media in early childhood education can effectively support Qur'an memorization, providing a foundation for future Islamic learning. Further research on its application in various educational settings is recommended. Highlights: Murojaah wheel media significantly improves young children's ability to memorize the Qur'an. Integrating interactive learning media supports Islamic education from an early age. The study fills a knowledge gap in the application of innovative teaching methods in religious education. Keywords: Murojaah Wheel Media, Quran Memorization, Early Childhood, Islamic Education, Learning Tools